Urban regeneration, Business Improvement Districts and retail revitalization: mind the gaps - Mendes, Luís (2022)
Urban regeneration refers to projects that are designed to revitalize and improve the quality of areas in cities, involving an investment of private or public funds, based upon an understanding of the shortcomings of particular cities and what makes cities great. This volume includes five chapters that explore the concept of urban regeneration from a variety of perspectives. Chapter One includes a review of the scientific literature regarding the origin of the concept of urban regeneration, discusses the assumptions and defining traits associated with urban regeneration, and addresses business districts and the challenges they pose to the retail revitalization of urban environments. Chapter Two examines how it is possible to produce urban regeneration while preserving the identity of historic centers and minimizing the negative impacts of gentrification. Chapter Three presents reflections on the lessons learned from urban regeneration processes in the context of Southern European countries, with a special focus on the case of Barcelona. Chapter Four presents a case study of the Knocknaheeny estate in Cork city, Ireland, where a multi-annual regeneration masterplan has been implemented since 2013. Lastly, Chapter Five focuses on the different continental backgrounds for expropriation in Germany and South Korea and includes specific case studies for residential redevelopment projects based on three categories: effectiveness, justice, and legitimacy.